Introduction to the Special Issue: Colonial past and intercultural relations. (January 2018) - Bobowik, Magdalena; Valentim, Joaquim Pires; Licata, Laurent
Abstract: The consequences of colonialism are important not only because they shape our "world of nations" at the level of international relations, but because their contemporary repercussions are also present in the psychosocial dynamics at work among former colonized and former colonizing peoples, such as identity building, collective emotions, traumatic processes, intergroup relations, prejudice, discrimination, and acculturation processes. However, there is still a scarce amount of cultural and social psychological studies dealing with the current implications of colonial history and memories in contemporary societies. This Special Issue aims to fill this gap. The main focus here is on the relevance of historical representations and collective memories of the colonial past with regard to contemporary intercultural relations. In this vein, this Special Issue includes eight papers that shed light on the content and structure of social representations of colonial history; the emotional and cognitive impacts of the colonial past; and how colonial past is shaping contemporary acculturation processes and intergroup attitudes and relations. This Special Issue hosts original empirical research employing different methodologies (e.g., interviews, questionnaire surveys, experiments, and case studies), as well as theoretical papers that rely on a systematic review of the empirical literature. Together, the contributions in this Special Issue stress the importance of considering colonial legacies in the study of contemporary intercultural relations. We call for dialogue and interdisciplinary work in this domain between social and cultural psychology and other social sciences, such as history, anthropology, and political science.